2016
DOI: 10.1017/s0007485316001127
|View full text |Cite
|
Sign up to set email alerts
|

Courtship and mating behaviour in the parasitoid waspCotesia urabae(Hymenoptera: Braconidae): mate location and the influence of competition and body size on male mating success

Abstract: Cotesia urabae is a solitary larval endoparasitoid that was introduced into New Zealand in 2011 as a classical biological control agent against Uraba lugens. A detailed knowledge of its reproductive biology is required to optimize mass rearing efficiency. In this study, the courtship and mating behaviour of C. urabae is described and investigated from a series of experiments, conducted to understand the factors that influence male mating success. Cotesia urabae males exhibited a high attraction to virgin femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 50 publications
1
12
0
Order By: Relevance
“…Outstanding pivotal position of body size in evolutionary biology and ecology research is given in particular by close relationships between body size and fitness components. For example, larger females are more fecund (Sota, ; Honěk, ; Marshall et al ., ; Pincheira‐Donoso & Hunt, ), whereas larger males often have a higher mating success (Savalli & Fox, ; Arriaga‐Osnaya et al ., ; Avila, Withers & Holwell, ). In addition, larger sized insects are frequently able to cope better with stressful environments.…”
Section: Introductionmentioning
confidence: 99%
“…Outstanding pivotal position of body size in evolutionary biology and ecology research is given in particular by close relationships between body size and fitness components. For example, larger females are more fecund (Sota, ; Honěk, ; Marshall et al ., ; Pincheira‐Donoso & Hunt, ), whereas larger males often have a higher mating success (Savalli & Fox, ; Arriaga‐Osnaya et al ., ; Avila, Withers & Holwell, ). In addition, larger sized insects are frequently able to cope better with stressful environments.…”
Section: Introductionmentioning
confidence: 99%
“…The displacement experiments showed that larger intact/muted males nearly always succeeded when they competed against smaller intact/muted males. Through these experiments, we confirmed that body size itself is an important factor determining the outcome of male‐male competition, as has been reported previously in other animals (Alcock, 1995; Hagelin, 2002; Chelliah & Sukumar, 2013; Benelli et al ., 2016; Avila et al ., 2017). When two males encountered each other, no matter their size, the dispute is settled by fighting in which the first male attempts to block the gallery by fighting to keep the intruder out of the gallery (see Video S1).…”
Section: Discussionmentioning
confidence: 99%
“…Courtship behavior of some Cotesia species has been studied to improve mass rearing in biological control programs (e.g. [21,42]). However, most species remain taxonomically undescribed and limited information is available beyond descriptions, host usage, and ranges for the majority of described species.…”
Section: Introductionmentioning
confidence: 99%